Tidal emersion effects on universal metrics, elemental contents, and health conditions of Pacific oyster (Crassostrea gigas) on artificial reefs in Yellow River Delta, China - Shen-Tong Wang; Wei Wang; Lu-Ping Wang; Li Li; Guo-Fan Zhang (Global Ecology and Conservation, 2023)
Oysters form natural reefs and are important coastal foundation species that provide a wide range of ecosystem services. Clarification of the mechanisms by which tidal emersion affects oyster reef performance will help guide and direct future oyster reef restoration efforts. In the present study, we constructed artificial Pacific oyster (Crassostrea gigas) reefs in the coastal zones of the Yellow River Delta and quantified the effects of tidal emersion on the growth, density, biomass, element (carbon, nitrogen, phosphorus) content within tissues, and health conditions of oysters. The results showed that temperature change driven by the tidal emersion effect was one of the major forces affecting reef performance. In the experimental field, fully immersed oysters performed better than partially exposed ones in terms of growth and density. The mean biomass of the fully immersed oysters was 2.88-fold higher than that of the partially exposed oysters (p < 0.05). However, we found that tidal emersion had no significant effect on the carbon, nitrogen, and phosphorus content within oyster tissues. Oyster health condition revealed by the biochemical marker and whole-genome gene expression analyses demonstrated that the oysters partially exposed to air presented enhanced oxidative and lipid metabolism and were forced to allocate metabolic energy towards defense against stress rather than growth, which suggested sub-optimal health conditions. Overall, the study indicated that full immersion is optimal for oyster reef restoration in the experimental field. The results of this research will provide future conservationists, aquaculturists, and other specialists with a better understanding of tidal emersion effects on the success of oyster reef restoration to achieve region-specific restoration goals and improve protection of the coastal environment.